KAJIAN MATEMATIS DISTRIBUSI TEKANAN PADA AIRFOIL JOUKOWSKY - MARYANTO, EDDY (MATEMATIKA, 2007)
The objectives of this research are to investigate the effect of the translation of the coordinate system to the shape of the Joukowsky airfoils formed and to compute lift coefficient of the Joukowsky airfoils. The result of the research is the higher the absisca and ordinate of the translation the higher the lift coefficient (with absisca must be greater than ordinate and  both are greater to zero).  If the circle is translated along positive x-axis, the airfoil formed is symmetrical with respect to x-axis.  While if it is  translated along positive y-axis, the airfoil formed is curve shaped.   From the research we also have found the fact the higher the distance of the translation from the center of the coordinate system the higher the thickness of the airfoil formed.